Application of a handheld Raman spectrometer for the screening of colored secondary sulfates in abandoned mining areas—The case of the São Domingos Mine (Iberian Pyrite Belt). (10th March 2020) - Košek, Filip; Culka, Adam; Fornasini, Laura; Vandenabeele, Peter; Rousaki, Anastasia; Mirao, Jose; Bersani, Danilo; Candeias, António; Jehlička, Jan
Abstract: The São Domingos area (Corte do Pinto, Portugal) represents a large sulfide ore deposit in the Iberian Pyrite Belt that was mined primarily for copper and sulfur in the past. Currently, the deserted mine and mine wastes are the reason for the production of acid mining drainage releasing potentially harmful elements. Because metastable secondary sulfates may temporary sink toxic pollutants, the in situ monitoring of their distribution is required. In this work, we tested a handheld Raman spectrometer equipped with a 532 nm laser excitation for this task. Twelve selected samples of complex composition were analyzed directly in the field using the handheld Raman spectrometer. For comparison, the collected samples were additionally analyzed through laboratory‐based Raman spectroscopy and X‐ray diffraction. Based on the in situ measurements, rozenite, melanterite, coquimbite, jarosite, metavoltine, chalcanthite, bonattite, antlerite, halotrichite‐group minerals, gypsum, and sulfur were detected. The results show that handheld Raman spectrometer is comparable with other laboratory techniques and such handheld systems can be deployed successfully for monitoring of sulfate distribution directly on site. Abstract : A handheld Raman spectrometer equipped with a 532 nm excitation source was tested for the in situ investigation of sulfates efflorescence of the AMD origin in the São Domingos area (Portugal). A suite of hydrated Fe‐, Cu‐, Mg‐, and Al‐bearing sulfates and elemental sulfur was detected in complex mixtures by the miniature spectrometer. The results obtained in the field are generally in agreement with the results obtained through the laboratory methods (Raman microspectroscopy and XRD) that were used as comparison.